Experimental Study on Shear Strengthening of Reinforced Concrete Beams Using Different Techniques of Concrete Jacketing - Ojaimi, Mohammed F. (Basrah Journal for Engineering Sciences, 2021)
A large number of RC structures or at least some of their members need strengthening or rehabilitation. Among the typical failure modes, the shear failure is more dangerous and less predictable, because of usually brittle behavior and sudden collapse. Therefore, there are necessities for upgrading the shear capacity and the local ductility of reinforced concrete beams. In this study, four different techniques of concrete jacketing were used to improve the behaviors of the shear deficiencies beams. The four techniques used in this study to enhance the behavior of the beams were by using a Self-Compacted Fiber Reinforced Concrete jacket without stirrups (S.-J. + Steel Fiber), a concrete jacket of Self Compacted Concrete with stirrups (S.-J. + Stirrups), a concrete jacket of ferrocement jacket (S.-J. + Ferrocement), and a concrete jacket of ferrocement jacket with external steel reinforcing bars (S.-J. + Ferrocement + R). These techniques contributed to enhancing the load-carrying capacity and delaying the appearance of the first crack in tested beams compared with the control beam by a percentage of (35, 59, 30, 6) % and (18, 35, 81, 80) %, respectively. The specimen (S.-J. + Stirrups) showed the best performance in comparison with the other used strengthening techniques used in this study in terms of stiffness and the ultimate load-carrying capacity. The ferrocement jacket (S.-J. + Ferrocement) was found to be the most suitable jacketing system used to enhance the shear capacity in terms of cracking load.